Servification of Firms and Trade Policy Implications - Magnus Lodefalk (Örebro University School of Business, 2016)
In the OECD countries, the decline of manufacturing and its employment implications have long been matters of concern. Recently, policymakers in several countries have set out to achieve reindustrialization. The servicification of firms is related to these concerns and aspirations. However, servicification and particularly its role in trade policy have received limited attention. I review micro-level evidence and discuss implications. I find that imported, domestic and exported services are all important to contemporary firm competitiveness and participation in international value chains. Therefore, historic policymaking divides between trade in manufactures and services, between export and import interests, and among modes of supply are becoming less relevant. I conclude by suggesting potential steps forward.
Additional information: Previous title: "Servification of Manufacturing Firms Makes Divides in Trade Policy-Making Antiquated"
Keywords: F13; F15; L16; L24; L60; O14; 330; Servicification; services; manufacturing; deindustrialization; offshoring; onshoring; trade; trade policy; GATT; WTO; Mode 4